A Diagnostically Challenging Case of Febrile Ulceronecrotic Mucha-Habermann Disease in an Adult Female Successfully Treated with Methotrexate and Cyclosporine - Tracy Ngo; Claudia Hossain; Jason Cohen; Beth McLellan; Rachel Blasiak; Eugene Balagula (Karger Publishers, 2021)
Febrile ulceronecrotic Mucha-Habermann disease (FUMHD) is a rare and severe variant of pityriasis lichenoides et varioliformis acuta (PLEVA) characterized by intermittent pyrexia, acute onset of generalized ulceronecrotic lesions, and histopathology suggestive of PLEVA. Prompt diagnosis and treatment are necessary to halt the progression of this potentially fatal disease; however, the widely variable presentation of FUMHD in addition to its rarity poses a diagnostic challenge. We report the case of a previously healthy 43-year-old woman who presented to the emergency department with 1 month of generalized rash and intermittent fevers. Her only reported new exposure were elective intravenous vitamin infusions received at a medi-spa 1 week prior to onset of lesions. Initial evaluations were inconclusive, and confluent ulceronecrotic, hemorrhagic lesions appeared on approximately 90% of her body despite steroid, antibiotic, and cyclosporine therapy. Repeat histopathology was consistent with PLEVA, and in the context of her clinical presentation she was diagnosed with FUMHD. The patient rapidly attained remission with methotrexate therapy but sustained residual scarring.